High-purity hydrogen production from ash-free coal by catalytic steam gasification integrated with dry-sorption CO2 capture. (15th August 2016) - Mostafavi, Ehsan; Mahinpey, Nader; Rahman, Moshfiqur; Sedghkerdar, Mohammad Hashem; Gupta, Rajender
Graphical abstract: Highlights: H2 was produced by ash-free coal catalytic steam gasification with CO2 capture. H2 purity up to 85% (on dry basis with N2 ) was achieved in a fixed bed reactor. The maximum gasification rate occurred with 20 wt% catalyst and Ca/C ratio of 2. Carbon conversion of 97% was measured by elemental CHNS analysis of the residues. CaO improves the H2 molar fraction while K2 CO3 enhances the overall reaction rate. Abstract: This study is aimed at the improvement of process conditions for catalytic steam gasification of ash-free coal (AFC) integrated with CO2 capture. A novel modified catalytic hydrogen production reaction integrated gasification (M-HyPr-RING) process was proposed for high-purity H2 production from steam gasification of AFC. AFC was prepared from lignite coal by solvent extraction with maximum yields of 67% on a dry ash free basis at 400 °C using hydrotreated heavy aromatic hydrocarbons with a coal-to-solvent ratio of approximately 1:10. The gasification temperature and sorbent-to-carbon (CaO/C) ratio were maintained constant for all experiments at 675 °C and 2, respectively, as determined by our previous findings. The steam gasification experiments were conducted on AFC in a fixed-bed reactor in the presence of different catalyst loadings (5, 10 and 20 wt% of potassium carbonate) with and without sorbent. A maximum hydrogen molar fraction of 85% (dry basis with nitrogen) was observed with catalyst loading of 20% and CaO/C of 2 after 5 min of steam gasification under mild process conditions.